Rhodium‐Alloyed Beta Gallium Oxide Materials: New Type Ternary Ultra‐Wide Bandgap Semiconductors - Xian‐Hu Zha; Yu‐Xi Wan; Shuang Li; Dao Hua Zhang (Advanced Electronic Materials)
Abstract Beta gallium oxide (β‐Ga2O3) is an ultra‐wide‐bandgap semiconductor with advantages for high‐power electronics. However, the power resistance of β‐Ga2O3‐based devices is still much lower than its material limit due to its flat band dispersion at its valence band maximum (VBM) and the difficulty for p‐type doping. Here, β‐Ga2O3‐based new type ternary ultra‐wide bandgap semiconductors: β‐(RhxGa1‐x)2O3’s alloys are reported with x up to 0.5. The energy and band‐dispersion curvature of β‐Ga2O3’s VBM are significantly enhanced via Rh‐alloying. Compared to that in β‐Ga2O3, the β‐(RhxGa1‐x)2O3’s VBMs increase more than 1.35 eV. The hole mass of β‐(Rh0.25Ga0.75)2O3 is only 52.3% of that in β‐Ga2O3. The decreased hole mass is correlated with the equal Rh─O bond along the b‐axis. Thanks to the simultaneous rise of conduction band minimums, the bandgaps of β‐(RhxGa1‐x)2O3 are still much larger than that in commercial silicon carbide. Moreover, the alloys show direct bandgaps in a wide range of x, and a direct and ultra‐wide bandgap of 4.10 eV is determined in β‐(Rh0.3125Ga0.6875)2O3. Combined with the enhanced valence energy, reduced hole mass, and ultra‐wide bandgap, the β‐(RhxGa1‐x)2O3 can be candidate semiconductors for a new generation of power electronics, ultraviolet optoelectronics, and complementary metal‐oxide‐semiconductor (CMOS) technologies.